The influence of fluid inclusions, organics, and calcite fabric on trace element distributions in stalagmites - Kost, O.; Sliwinski, J.; Gies, N.; Lueder, M.; Stoll, H. (Frontiers in Earth Science, 2023)
Trace elements and calcite fabrics in stalagmites are increasingly employed as indicators of past environmental conditions. The drivers of trace element concentrations and fabrics reflect a complex interplay of factors during crystal growth, and accurate interpretation of geochemical proxies requires a clear understanding of the incorporation of the proxy signal in the stalagmite. We employ a series of non-destructive techniques to compare the spatial distribution of water, organic components, and trace elements and in relationship with calcite fabrics, and evaluate if these distributions are consistent with recent hypotheses about controlling factors on crystal fabrics, fluid inclusions, and element incorporation. We use for the first time Fourier Transformation Infrared Focal-Plane Array (FTIR-FPA) imaging to show the distribution of molecular water (3,400 cm−1 absorbance) and organic matter (2,983 cm−1) in calcite. To test if entrapped water in speleothem calcite affects the abundance or distribution of trace elements, the element distribution (Na, Mg, Sr, U, Al, Y, and Zn) is mapped by Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA-ICP-MS). Transmitted Light Microscope imaging constrains crystal fabrics. We find that stalagmite areas with strong Organic Matter fluorescence via Confocal Laser Scanning Microscopy coincide with areas of high Fourier Transformation Infrared absorbance at 2,983 cm−1, suggesting common co-location of multiple organic matter types in the stalagmite. While microscopic fluid inclusions visible in transmitted light are also detected by FTIR 3400 cm−1 absorbance, the FTIR additionally detects submicroscopic fluid inclusions, but not evident in transmitted light microscopy. In most samples, Na concentration is elevated in regions of high fluid inclusion density, suggesting that a significant portion of Na may be hosted in entrapped water rather than in the calcite. Only samples with 100-fold higher Y, feature Na concentrations which appear dominated by coupled Y-Na substitution and little influenced by fluid inclusion hosted Na. Our analysis provides new evidence of the influence of fluid inclusions on trace element content of stalagmites and illustrates the utility of several non-destructive imaging techniques to improve interpretations of proxy signals based on trace elements.